UPAYA MENINGKATKAN HASIL BELAJAR SISWA PADA BIDANG STUDI MATEMATIKA MATERI SEGITIGA MELALUI STRATEGI JIGSAW DI KELAS VII MTs. SWASTA DARUL FALAH KABUPATEN LABUHAN BATU SELATAN TAHUN PELAJARAN 2014/2015 - Nova Astina (AXIOM : Jurnal Pendidikan dan Matematika, 2016)
The purpose of this study was want to know (1) student's learning resultbefore taught by jigsaw strategy in the material triangle, (2) the level ofstudents achievement after being taught by jigsaw strategy in thematerial triangle, (3) student's responses to the application of the jigsawstrategy in the material triangle. This study uses research grade level,consist of two cycles. This study was done in grade VII in MTs. SwastaDarul Falah district south Labuhanbatu, the number of students are 33students, used data collection teqniques are observation, test andinterview. test done 3 time that are initial test, the result of learning 1and the result learning 2. Mathematic learning result of students beforegiving jigsaw strategy, obtained the students who have master as much12 students (36,40%) and 21 students (63,63%) who have not master.After giving jigsaw strategy in the first cycle, obtained the students whohave master 14 students (42,42%) and 19 students (57,60%) who havenot master. Furthermore after giving second cycle, obtained 30 students(90,90%) who have master, and 3 students (9,1%) who have not master,so by the first cycle and the second cycle an increase of 48.48%. Basedon the results of this study concluded that the application of the jigsawstrategy to improve mathematic learning result of students in grade VIIMTs. Swasta Darul Falah district south Labuhanbatu.